Factors Influencing Marital Stability - Maciver, J. E.; Dimkpa, D. I. (Mediterranean Journal of Social Sciences, 2012)
The marital institution is witnessing instability globally. This study investigated factors that influence marital stability asperceived by literate spouses in Yenagoa metropolis of Bayelsa State, Nigeria. The population of this study consist of all literatemarried couples in Yenagoa metropolis. A total of 600 respondents were selected using the simple random sampling technique.The instrument titled â€œFactors Influencing Marital Stability Questionnaireâ€ (FIMSQ) was used in collecting the relevant data, withPearson reliability (r) of 0.78. Mean scores were used to analyze the main research question; Analysis of variance (ANOVA) andthe t-test statistics were used to test four null hypotheses generated for the study. The findings showed that in order of ranking,social, behavioural, domestic, sexual, religious and financial factors influence marital stability. It further showed that there wereno significant differences among the respondents in their perception of factors influencing marital stability based on gender,religion, educational level and length of marriage. Thus, some recommendations were made in line with the findings.